Transmembrane Signaling Protocols - Ali, Hydar; Haribabu, Bodduluri; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2006)
The complete sequencing of the human genome and many new microarray and proteomic methods for analyzing global changes in both gene expression and protein profiles have greatly increased our ability to understand transmembrane signaling processes in close detail. In this fully updated and expanded second edition of Transmembrane Signaling Protocols, leading experts demonstrate the use of such techniques as single-cell imaging, bioluminescence resonance energy transfer, and global proteomics in the study of transmembrane signaling events. Highlights include the functional expression and genetic selection of mutant mammalian transmembrane receptors in yeast, real-time analysis of transmembrane receptor signaling in live cells, and bioluminescence energy transfer to monitor protein-protein interaction. Additional chapters use state-of-the-art methods to analyze gene expression and proteomic profiles related to transmembrane signaling events, as well as to genetically reconstitute bone marrow for the study of signal transduction ex vivo. Introductory chapters provide a wide-ranging perspective, including an overview of the many recent advances in our understanding of signal transduction pathways. The protocols follow the successful Methods in Molecular Biology$1!" (Bseries format, each offering step-by-step laboratory instructions, an introduction outlining the principles behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Cutting-edge and highly practical, Transmembrane Signaling Protocols, Second Edition, makes available to novice and experienced researchers alike the readily reproducible techniques needed to advance the study of signal transduction pathways today.s
Overviews -- Transmembrane Signaling by G Protein-Coupled Receptors -- Crosstalk Coregulation Mechanisms of G Protein- Coupled Receptors and Receptor Tyrosine Kinases -- Protein-Protein Interactions in Signaling Cascades -- Specific Topics -- Biological Role of the CXCR4-SDF-1 Axis in Normal Human Hematopoietic Cells -- Functional Expression of CXCR4 in Saccharomyces cerevisiae in the Development of Powerful Tools for the Pharmacological Characterization of CXCR4 -- Characterization of Constitutively Active Mutants of G Protein-Coupled Receptors -- G Protein-Coupled Receptor Dimerization and Signaling -- Real-Time Analysis of G Protein-Coupled Receptor Signaling in Live Cells -- Isolation of Membrane Rafts and Signaling Complexes -- Methods for the Study of Signaling Molecules in Membrane Lipid Rafts and Caveolae -- Bioluminescence Resonance Energy Transfer to Monitor Protein-Protein Interactions -- Identification of Interacting Proteins Using the Yeast Two-Hybrid Screen -- Analysis of PDZ Domain Interactions Using Yeast Two-Hybrid and Coimmunoprecipitation Assays -- Clustering Assay for Studying the Interaction of Membrane Proteins with PDZ Domain Proteins -- Mammalian Cell Microinjection Assay to Study the Function of Rho Family Guanosine Triphosphatases -- Affinity-Based Assay of Rho Guanosine Triphosphatase Activation -- Assay of Phospholipase D Activity in Cell-Free Systems -- Reconstitution System Based on Cytosol-Depleted Cells to Study the Regulation of Phospholipase D -- Analysis of Global Gene Expression Profiles Activated by Chemoattractant Receptors -- Genetic Reconstitution of Bone Marrow for the Study of Signal Transduction Ex Vivo -- Proteomic Analysis of Human Neutrophils.
Keywords: Life sciences; Cell biology; Life Sciences; Cell Biology; Electronic books